Virological and Biochemical Effects of Tenofovir Alafenamide in Different Patient Groups With Chronic Hepatitis B Virus Infection in Real-World Cohort - Erdem Bektas; Aysenur Yilmaz; Cevat Ilteris Kikili; Kanan Nuriyev; Zulal Istemihan; Ibrahim Volkan Senkal; Ziya Imanov; Bilger Cavus; Asli Cifcibasi Ormeci; Filiz Akyuz; Kadir Demir; Selman Fatih Besisik; et al. (International Journal of Hepatology)
Hepatitis B virus (HBV) infection is an important health concern worldwide. HBV infection can lead to acute hepatitis, cirrhosis, hepatocellular carcinoma, liver failure, and death. Nucleos(t)ide analogs (NAs) form the core of the HBV treatment. The safety and efficacy of NAs in long-term follow-up are still critical issues. We enrolled 225 consecutive patients with at least 12 months of longitudinal follow-up using tenofovir alafenamide (TAF), including 39 antiviral naïve and 186 antiviral experienced patients. In the treatment-experienced group, the main reasons for switching from other NAs to TAF were renal dysfunction and osteoporosis. Renal outcome, lipid profile, virological response, and ALT normalization under the TAF treatment were evaluated. Age > 60 years, liver transplant recipients, and patients with decompensated cirrhosis were evaluated separately, as well as the total cohort. Phosphorus levels increased especially in hypophosphatemic individuals, eGFR levels also increased slightly but statistically significantly, and the remarkable improvement in eGFR stages was observed in the eGFR < 60 mL/min/1.73 m2 group. A minimal increase in LDL-c levels occurred after TAF treatment, which did not reach statistical significance. Total cholesterol and HDL-c levels increased significantly, while triglyceride levels remained unchanged. In the total cohort, HBV-DNA was strongly suppressed in either treatment-naïve or experienced patients. ALT and AST levels decreased with the TAF treatment, but ALT normalization rate did not change significantly. No serious adverse events associated with TAF occurred, and discontinuation was not required in the total cohort. Our findings support that TAF treatment is well-tolerated and effective in patients with chronic HBV infection.